The European War : documents relating to the negotiations which preceded Germany's declaration of war on Russia (August 1, 1914) and on France (August 3, 1914) : declaration of September 4, 1914. (S.l. : Ministry of Foreign Affairs, 1914)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Wereldoorlog 1